2010
DOI: 10.1186/1476-4598-9-280
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of extracellular matrix/adhesion molecule expression by BRG1 is associated with increased melanoma invasiveness

Abstract: BackgroundMetastatic melanoma is an aggressive malignancy that is resistant to therapy and has a poor prognosis. The progression of primary melanoma to metastatic disease is a multi-step process that requires dynamic regulation of gene expression through currently uncharacterized epigenetic mechanisms. Epigenetic regulation of gene expression often involves changes in chromatin structure that are catalyzed by chromatin remodeling enzymes. Understanding the mechanisms involved in the regulation of gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 71 publications
5
46
0
Order By: Relevance
“…Taken together, these results suggest that SMARCA4 positively regulates genes associated with ECM, supporting the role for SMARCA4 in ECM biology (Xu et al 2007;Stankunas et al 2008;Saladi et al 2010), and negatively regulates genes related to lipid metabolism and calcium signaling in mammary epithelial cells. Moreover, SMARCA4 also regulates the expression of many lncRNAs.…”
Section: Smarca4 Globally Affects Gene Regulation In Mcf-10a Cellsmentioning
confidence: 56%
“…Taken together, these results suggest that SMARCA4 positively regulates genes associated with ECM, supporting the role for SMARCA4 in ECM biology (Xu et al 2007;Stankunas et al 2008;Saladi et al 2010), and negatively regulates genes related to lipid metabolism and calcium signaling in mammary epithelial cells. Moreover, SMARCA4 also regulates the expression of many lncRNAs.…”
Section: Smarca4 Globally Affects Gene Regulation In Mcf-10a Cellsmentioning
confidence: 56%
“…Expression of Smarcd1/Baf60a and Smarca4/Brg1 were both significantly higher in mEpiSCs than mESCs. Interestingly, Smarcd1/Baf60a mediates the interaction between several signaling pathways and BAF complexes (40). In human cells, a direct interaction between p53 with SMARCD1/BAF60A (but not between p53 and SMARCA4/BRG1) has been reported (41).…”
Section: Discussionmentioning
confidence: 99%
“…36 Yet another study indicated that BRG1 messenger RNA levels were significantly higher in stage IV melanoma samples compared to normal and stage III melanoma samples. 60 Interestingly, recent exome sequencing studies have detected BRG1 mutations at a low frequency in patient-derived melanoma samples 53 (Table 1). These studies suggest that BRG1 function may be compromised in a small subset of melanomas.…”
Section: Melanomamentioning
confidence: 99%
“…24,46 The requirement for SWI/SNF activity is associated with MITF-dependent and -independent functions. 24,36,46,47,60 …”
Section: Melanomamentioning
confidence: 99%